2007
DOI: 10.1007/s00134-007-0602-6
|View full text |Cite
|
Sign up to set email alerts
|

Plethysmographic dynamic indices predict fluid responsiveness in septic ventilated patients

Abstract: Objectives: In septic patients, reliable non-invasive predictors of fluid responsiveness are needed. We hypothesised that the respiratory changes in the amplitude of the plethysmographic pulse wave (∆P PLET ) would allow the prediction of changes in cardiac index following volume administration in mechanically ventilated septic patients. Design: Prospective clinical investigation. Setting: An 11-bed hospital medical intensive care unit. Patients: Twenty-three deeply sedated septic patients mechanically ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 26 publications
3
86
2
2
Order By: Relevance
“…Cannesson et al for their kind comments regarding our contribution [1]. We fully agree with these authors that pulse oximeters use digital signal processing to make accurate measurements in clinical conditions that were otherwise impossible (e. g., patient motion, low perfusion, electrical interference).…”
supporting
confidence: 75%
“…Cannesson et al for their kind comments regarding our contribution [1]. We fully agree with these authors that pulse oximeters use digital signal processing to make accurate measurements in clinical conditions that were otherwise impossible (e. g., patient motion, low perfusion, electrical interference).…”
supporting
confidence: 75%
“…With transthoracic echocardiography, it is easy to demonstrate the dilation and decrease of diameter of the inferior caval vein (IVC) with inspiration and expiration, respectively. Barbier et al and M Feissel et al demonstrated clearly that respiratory variation of the IVC reliably predicts fluid responsiveness [20,21]. Conversely, in acutely decompensated heart failure patients, the rate of fluid withdrawal during haemodialysis can be guided by intermittent evaluation of the respiratory induced alterations of the IVC diameters [22].…”
Section: Mechanical Ventilator Induced Intra-thoracic Pressure Changementioning
confidence: 99%
“…10,16 Pulse pressure variation (PPV) and systolic pressure variation (SPV)-both derived from analysis of the arterial waveform-, stroke volume variation (SVV), and the variation of the amplitude of the pulse oximeter plethysmographic waveform are predictive of fluid responsiveness. 7,21,22 These techniques use heart-lung interactions during mechanical ventilation. During inspiration, pleural pressure increases, causing a reduction in RV preload and an increase in RV afterload.…”
Section: Dynamic Variablesmentioning
confidence: 99%